(Non)corporeality in Online Studies - Reflections of Researchers on Conducting Online Focus Interviews - Katarzyna Miśkiewicz; Gabriela Dobińska (Jesuit University Ignatianum in Krakow, 2023)
RESEARCH OBJECTIVE: The aim of the article is to consider the presence and significance of the body in designing and conducting remote (online) ethnographic (field research) studies. THE RESEARCH PROBLEM AND METHODS: The research problem refers to answering the following question: What is the significance of corporeality in conducting remote (online) studies? In attempting to answer the research question we made use of autoethnography, treating it as method and research strategy. THE PROCESS OF ARGUMENTATION: Inspired by the conclusions drawn by Anna Kacperczyk regarding ways of defining corporeality in ethnographic studies, the authors intend to present their reflections regarding their own research conducted in virtual space in 2021. These considerations refer to studies on academic education during the pandemic. RESEARCH RESULTS: Reflections on corporeality in ethnographic studies allowed us to frame our experiences in three dimensions (perspectives): the body as a source of individual corpore- al experiences, the body (corporeality) of the researcher and of the respondent during an ethno- graphic study and the body as a topic of individual self-reflection and as a subject for theorizing. CONCLUSIONS, INNOVATIONS, AND RECOMMENDATIONS: (Non)corporeality turned out to be ambiguous, thus we decided to treat it in a multidimensional manner, considering corporeality as a value regardless of the circumstances of the study (in-person vs online). The significance and role of the body in ethnographic studies conducted remotely (online) are equally important to those in studies conducted in-person (traditionally). In remote studies corporeality is restricted to some extent for both researcher and respondent, however, focusing on other sensory impressions (e.g. auditory) allows us to experience another dimension of corporeality.